Comparison of Pigmented Lesions that Appear in the Mouth of Smokers and Passive Smokers - Raida Noori Hamid; Shakir Mahmood Ali; Lara Kusrat Hussein (Wolters Kluwer Medknow Publications, 2021)
Introduction: Passive smoker individuals whom live near the smokers and pigmentation appears on their oral mucosa due to proximity from smokers. Materials and methods: This study was carried-out on 50 patients suffering from pigmentation of the mouth that were collected from the private dental clinic were obtained and 50 individual's neighbouring to them and considered as the passive smoking group. Discussion: For passive smoker the pigmentation increasing with duration of smoking, in non-filtered cigarettes than filtered cigarette and in heavy smokers than mild smokers The intraoral distribution of melanin pigmentations commonly observed in the buccal region, Lingual, gingival and palatal of the mouth.